CultureShock! Malaysia a survival guide to customs and etiquette - Munan, Heidi (Cultureshock!, 2005)
Born in 1963 through the merging of four independence movements, Malaysia today consists of West, or Peninsular, Malaysia and East Malaysia -- Sabah and Sarawak on the island of Borneo. While pursuing economic progress, Malaysia is preserving its cultural and natural environments, which hold the history of the country's people and wildlife. Malaysia is a leader in the Association of Southeast Asian Nations (ASEAN) and an energetic participant in world affairs. The country's future is being shaped by an increasing literate population. Working Malaysians are constantly upgrading their knowledge and skills, while younger generations are obtaining degrees and diplomas at universities and other institutes at home and abroad. Malaysia's urban landscapes are getting bigger and taller, and Kualar Lumpur, its capital city, boasts the tallest building in the world, the Petronas Twin Towers. Cultures of the World: Malaysia looks at the varied landscapes, lifestyles, languages, faiths, festivals, foods, and arts that make the land and people of Malaysia.